(untitled) (International Seven Journal of Multidisciplinary, 2025)
In the modern digital world, safeguarding sensitive data and managing access to critical systems are essential for organizations. Identity and Access Management (IAM) is a key framework for controlling access to systems and data, ensuring only authorized users can gain access. Traditionally relying on static methods like passwords, IAM systems are now facing challenges due to the complexity of cyber threats and the increasing number of users and devices. To address these issues, AI is transforming IAM by improving user authentication, detecting security anomalies, and refining permission management. AI contributes to user authentication through biometric technologies like facial recognition, fingerprint scanning, and voice recognition, reducing vulnerabilities from traditional methods. Machine learning also enhances authentication by continuously analyzing user behavior, adapting systems to recognize legitimate users more accurately. Additionally, AI plays a vital role in anomaly detection by analyzing user activity data across various platforms and identifying unusual patterns that indicate potential threats. AI’s impact extends to dynamic and context-aware permission management, offering real-time adjustments based on factors such as user role and location. Furthermore, AI supports continuous risk assessment and regulatory compliance by monitoring user activities and ensuring proper access controls. The integration of AI in IAM also strengthens cloud security, as seen in the research of Muppa (2022), Mandru (2022), Oduri (2019), Mohammed (2021), Ramakrishnan (2021), and Subburaman (2022), who explore how AI helps mitigate emerging threats, optimize authentication, and improve access control in cloud environments. Ultimately, AI in IAM offers a more adaptive, resilient, and precise solution to evolving security challenges. Organizations adopting AI-powered IAM systems will be better equipped to face future cyber threats, ensuring both data protection and operational continuity.